Development of a luciferase-based reporter of transcriptional gene silencing that enables bidirectional mutant screening in Arabidopsis thaliana - Won, So Youn (BioMed Central, 2012)
BACKGROUND: Cytosine methylation is an important chromatin modification that maintains genome integrity and regulates gene expression through transcriptional gene silencing. Major players in de novo methylation guided by siRNAs (known as RNA-directed DNA methylation, or RdDM), maintenance methylation, and active demethylation have been identified in Arabidopsis. However, active demethylation only occurs at a subset of RdDM loci, raising the question of how the homeostasis of DNA methylation is achieved at most RdDM loci. To identify factors that regulate the levels of cytosine methylation, we aimed to establish a transgenic reporter system that allows for forward genetic screens in Arabidopsis. RESULTS: We introduced a dual 35 S promoter (d35S) driven luciferase reporter, LUCH, into Arabidopsis and isolated a line with a moderate level of luciferase activity. LUCH produced transgene-specific 24 nucleotide siRNAs and its d35S contained methylated cytosine in CG, CHG and CHH contexts. Treatment of the transgenic line with an inhibitor of cytosine methylation de-repressed luciferase activity. Mutations in several components of the RdDM pathway but not the maintenance methylation genes resulted in reduced d35S methylation, especially CHH methylation, and de-repression of luciferase activity. A mutation in MOM1, which is known to cooperate with RdDM to silence transposons, reduced d35S DNA methylation and de-repressed LUCH expression. A mutation in ROS1, a cytosine demethylation enzyme, increased d35S methylation and reduced LUCH expression. CONCLUSION: We developed a luciferase-based reporter, LUCH, which reports both DNA methylation directed by small RNAs and active demethylation by ROS1 in Arabidopsis. The moderate basal level of LUCH expression allows for bi-directional genetic screens that dissect the mechanisms of DNA methylation as well as demethylation.